Fitting in Versus Learning: A Challenge for Migrants Learning Languages Using Smartphones. Issue 1 (22nd February 2017) - Gaved, Mark; Peasgood, Alice
There is great interest in the potential of smartphones to enable language learning during daily activities. However, this overlooks the paradox faced by migrant learners that while they have the educational goal of seeking to improve their language skills, they also have the cultural goal of fitting into the host society. Inappropriate use of smartphones as learning aids makes learners stand out as outsiders. Here, we investigate the use of smartphones by migrants for Mobile Assisted Language Learning (MALL) in their daily lives. We report on their participation in the trial of a system that coupled a custom smartphone app with location-based hardware triggers. This presented learning activities based on scenarios from everyday life that were prompted when approaching relevant locations around a UK town. Analysis of pre- and post- interviews indicates that social and cultural influences affect the location, timing and type of learning undertaken using the system. Participants preferred to learn in ways that were unobtrusive, and deferred engagement with content if social context inhibited use of the phone. For example, playing audio in public was seen as inappropriate. Although the app was designed with location-specific content, many participants chose to study elsewhere and at other times, in addition to accessing content from the phone at the time and place that the activity was triggered. We conclude that social context and wanting to belong are important influences for migrant learners, and emphasise the potential of MALL systems in encouraging engagement with physical and digital spaces and reflections about citizenship.